Achyranthes bidentata polysaccharide suppresses osteoclastogenesis and bone resorption via inhibiting RANKL signaling. Issue 6 (9th March 2018) - Song, Dezhi; Cao, Zhen; Huang, Song; Tickner, Jennifer; Li, Nan; Qiu, Heng; Chen, Xi; Wang, Chao; Chen, Kai; Sun, Youqiang; Dong, Shiwu; Xu, Jiake
Abstract: Osteoclasts are highly differentiated multinucleated giant cells that play fundamental roles in bone resorption and in the pathogenesis of osteolytic conditions, such as osteoporosis and cancer‐induced bone loss. Achyranthes bidentata polysaccharide (ABP) is a hydrophilic compound with anti‐oxidation and anti‐aging characteristics. The impact of ABP on RANKL‐induced osteoclast formation and bone resorption has not been assessed, hence, in this study we investigated the effect of ABP on osteoclast formation and resorption in murine bone marrow derived osteoclasts. We found that ABP was able to suppress RANKL‐induced osteoclast differentiation and bone resorption activity at concentrations above 6.5 µM, while demonstrating no cytotoxicity at concentrations up to 10 µM. The actions of ABP were mediated through inhibition of RANKL‐induced c‐Fos and NFATc1 gene and protein expression. Furthermore, we found that ABP suppressed NFATc1 transcriptional activity, and the phosphorylation of MAPK pathways induced by RANKL. Collectively, ABP attenuates RANKL‐mediated osteoclast activity and signaling, and might serve as a potential therapeutic candidate for preventing bone loss related diseases. Abstract : ABP decreased the expression of NFATc1, TRAcP, Integrin β3, and CTSK via suppressing the phosphorylation of p38, JNK, and ERK, by which to inhibit RANKL induced osteoclast differentiation and function.